O64: GENOMIC PROFILING USING CIRCULATING NUCLEIC ACIDS IN STAGE IV MELANOMA PATIENTS RECEIVING IMMUNOTHERAPY REVEALS A NOVEL GENE AMPLIFICATION LANDSCAPE AND ALLOWS FOR DETECTION OF ACTIONABLE GENE MUTATIONS. (27th April 2021) - Ita, M; Wang, JH; O'Leary, P; Nolan, Y; Toulouse, A; Heffron, C; Power, D; Redmond, HP
Abstract: Introduction: Serial monitoring for disease progression and therapeutic efficacy at the molecular level in metastatic melanoma is hampered by a lack of reliable blood borne biomarkers. Molecular profiling of melanoma tumours is almost impractical in metastatic disease due to risks of procedure related morbidity and sampling inefficiency in representing tumour heterogeneity. Cell free DNA allows monitoring of molecular changes in melanoma over the course of immunotherapy. We investigated the utility of somatic mutation and gene amplification analyses in melanoma patients receiving immunotherapy. Method: Cell free DNA was extracted from plasma using a QIAamp Circulating Nucleic Acid Kit (Qiagen). Pathway focused profiling of somatic mutation status was performed by ARMs PCR using QBiomarker Somatic Mutation PCR Arrays (Qiagen). Gene amplification analysis was performed by Real Time Quantitative PCR (Roche) using RT 2  Profiler PCR Arrays (Qiagen). Result: A total of twenty patients with stage IV melanoma receiving immunotherapy were enrolled in this study. The BRAF p.V600E mutation was detected in the cfDNA of 80% of BRAF positive patients. Cell free DNA was also profiled for a total of 84 genes of the cancer inflammation and immunity pathway. There was a significant difference in the copy numbers of several genes (CTLA-4, CXCL12, CXCL5, IDO1, TGFB, IFNG, IL4, PTGS2, AICDA, HLA-A, CCL4, ACKR3, TP53, MYC) between patients with progressive disease and therapeutic response (n=20,   p  < 0.05). Conclusion: We postulate that cell free DNA pathway focused somatic mutation and gene amplification analyses may be useful in evaluating disease progression and therapeutic response. Take-home message: Genomic analysis of circulating nucleic acids may be useful in evaluating disease progression and therapeutic response in metastatic melanoma.